HUMAN RIGHTS : THE RIGHT TO MAKE A COMPLAINT - Chinda, Yaowaret (Journal of Graduate MCU KhonKaen Campus, 2021)
Human Rights: The Right to File a Complaint At present, emphasis is placed on the protection of rights. of the accused The right to file a complaint concludes that people have a right to complain. in various matters and has the right to sue a government agency. Section 61. A person shall have the right to submit a complaint. and be notified of the result of the consideration within a reasonable time as provided by law. Section 62 the right of a person to sue or government organizations that is a legal entity to be liable for the action or omission